A study of long-term soil moisture dynamics: assessing biologically available water as a function of soil development - Salley, Shawn William, author; Kelly, Eugene F., advisor; Martin, Patrick H., advisor; Knapp, Alan, committee member; Kahosla, Raj, committee member (Colorado State University. Libraries, 2015)
Forecasting ecosystem responses to global change is highly uncertain in light of the alarming rates of climate change predicted by the scientific community. Rising CO₂ concentrations not only cause increased warming, but may also influence the amount and distribution of rainfall in terrestrial ecosystems. This in turn affects plant growth and the ability of ecosystems to perform important functions including nutrient cycling and decomposition. Soil moisture is considered the major control of ecosystem structure and function, and it is considered the most limiting resource to biological activity in semi-arid grassland ecosystems. Total soil moisture potentials are controlled by edaphic properties such as texture, structure, micro-porosity, bulk density, soil depth, clay mineralogy, and organic matter content. Physical and chemical properties interact with hydrologic inflows and outflows to control soil moisture causing the soil to act as a store and regulator in the water flow system of the overall ecosystem. Thus, the soil acts as both temporary storage of precipitation inputs and as a regulator controlling the partition between inputs and the major outflows: evapotranspiration, runoff, leaching, and flow between organisms. Understanding the pedologic controls of water retention is critical in considering the long-term dynamics of ecosystems and projecting the consequence of global change. The focus of my dissertation is twofold: to elucidate the change in water holding characteristics of soils through pedogenesis and to quantify how global change will impact soil moisture in the U.S. Great Plains. In order to best address my research questions, I began by studying two established soil-chronosequences in northeast Colorado and central Wyoming to assess the characteristics of soil's physical and chemical properties. I examined how they control the biologically available water holding capacities that change predictably as a function of soil age. Next, I examined other notable soil chronosequences across the western United States to test the millennial evolution of soil water holding capacities through various climates and soil parent materials. Finally, I used a soil moisture simulation to spatially model the historical, contemporary, and future projections of soil moisture on the Great Plains. I found in semi-arid ecosystems that three broad stages of soil development exist and are linked to landscape ages that are ecologically and biogeochemically significant: aggrading, equilibrium, and retrogressive stages. Soils in the aggrading stage are typically weakly developed, have genetically simple horizon differentiation, and minimal water retention. Prominent clay and carbonate features are expressed in the equilibrium stage soils which show more complex soil horizonation, structure, aggregation, and porosity. Within these intermediate soils, the capacity to store water reaches a maximum. Declining or retrogressive stage soils show losses of clays and carbonates, have undergone extensive leaching, and the soil's capacity to store water is at a minimum compared to the aggrading and equilibrium stages. Furthermore, I confirmed when modeling soil moisture in the Great Plains that course-textured landscapes store less soil water and when accompanied with disturbance are more vulnerable to climate change. Overall, my dissertation focuses on understanding the role pedogenesis has on soil water holding characteristics and how global change impacts semiarid landscapes. My results have helped improve understanding of long-term ecosystem biophysical feedbacks through quantifying soil moisture retention characteristics across soil age and climatic processes by linking soil water properties to climatic and pedogenic variables.
Keywords: soil geomorphology; pedology; soil moisture